DRIVERS OF BUSINESS SUCCESS IN JEMBER’S COFFEE ANGKRINGAN MSMEs - Apriansah, Noval Dias; Fatimah, Feti; Rahayu, Jekti (Univesitas Muhammadiyah Tangerang, 2025)
The rapid growth of coffee angkringan micro, small, and medium enterprises (MSMEs) in Jember Regency highlights the potential of traditional food and beverage businesses among young entrepreneurs. However, the determinants of their success remain underexplored. This study examines the impact of innovation, risk-taking, digital marketing, entrepreneurial knowledge, and motivation on the business success of coffee angkringan MSMEs, addressing a gap in literature concerning traditional MSMEs in emerging economies. Using a quantitative approach, data were collected from 112 respondents and analyzed through multiple linear regression. The findings reveal that risk-taking significantly enhances business success, while innovation, digital marketing, entrepreneurial knowledge, and motivation show no significant effects. This study contributes by: (1) Identifying risk-taking as the primary driver of success in traditional MSMEs, contrasting with prior studies that emphasize innovation or digital tools; (2) Providing empirical evidence on the limited impact of digital marketing in informal business sectors, suggesting context-specific adoption challenges; and (3) Offering practical insights for policymakers and entrepreneurs to prioritize strategic risk management over conventional capacity-building approaches. The novelty of this research lies in its focus on angkringan—a unique blend of traditional and modern coffee MSMEs—and its challenge to common assumptions about entrepreneurial success factors in rural Indonesian contexts. These findings underscore the importance of adaptive strategies tailored to local business environments.